Analisis Kualitas Air dan Tingkat Pencemaran Limbah Cair Industri Tahu di Aliran Sungai Desa Ngumpul Kecamatan Jogoroto Kabupaten Jombang - Indah Nur Fadhilah; Bambang Hariyanto (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The tofu industry is one of the business sectors that has developed rapidly in Jogoroto District, Jombang Regency, particularly in Ngumpul Village, Sumbermulyo Village, and Mayangan Village. However, tofu production activities generate wastewater containing high levels of organic matter, which has the potential to pollute water bodies if discharged without proper treatment. This study aimed to determine water quality and analyze the level of pollution caused by tofu industry wastewater in the Ngumpul Village River, Jogoroto District, Jombang Regency. This study employed a quantitative descriptive method using a purposive sampling technique at three observation points: B1 (500 m upstream from the wastewater discharge point), B2 (at the wastewater discharge point), and B3 (900 m downstream from the discharge point). The parameters analyzed included Total Suspended Solids (TSS), pH, Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The pollution level was determined using the Pollution Index (PI) method based on Government Regulation Number 22 of 2021 and the Decree of the Minister of Environment Number 115 of 2003. The results showed that water quality at point B1 still met the established quality standards, with a PI value of 0.99 (good category). At point B2, a significant increase in pollution was observed, with a PI value of 28.52 (heavily polluted category), while point B3 indicated a natural recovery process of the river but remained in the heavily polluted category, with a PI value of 10.59. These findings indicate that wastewater from the tofu industry has a significant impact on the decline of river water quality, particularly in the BOD, COD, TSS, and pH parameters. The impacts may disrupt aquatic ecosystems, agricultural activities, and public health. Therefore, more effective wastewater management is required through the construction of Wastewater Treatment Plants (WWTPs), regular water quality monitoring, and increased environmental awareness among tofu industry operators.